2022
DOI: 10.29271/jcpsp.2022.03.313
|View full text |Cite
|
Sign up to set email alerts
|

HALP Score as a New Prognostic Index in Metastatic Renal Cell Cancer

Abstract: Objective: To evaluate prognostic significance of the new index, designed by formulating hemoglobin, albumin, lymphocyte, and platelet (HALP) counts in patients with metastatic renal cell carcinoma (RCC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The most common abnormalities, linked to chronic inflammatory processes accompanying neoplasia, are represented by leukocytosis, neutrophilia, thrombocytopenia, and lymphocytopenia. These may occur during the growth and lysis of the tumor [ 17 , 25 , 26 ]. The positive feedback of immunoregulatory cytokines in the recruitment of tumor-associated neutrophils induces disease progression and increases the risk of distant metastasis; platelets also appear to have a similar role.…”
Section: Discussionmentioning
confidence: 99%
“…The most common abnormalities, linked to chronic inflammatory processes accompanying neoplasia, are represented by leukocytosis, neutrophilia, thrombocytopenia, and lymphocytopenia. These may occur during the growth and lysis of the tumor [ 17 , 25 , 26 ]. The positive feedback of immunoregulatory cytokines in the recruitment of tumor-associated neutrophils induces disease progression and increases the risk of distant metastasis; platelets also appear to have a similar role.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in 2022 Ekinci et al, analyzed 123 metastatic renal cell carcinoma patients and found a HALP score cutoff of 0.277 using the ROC curve [ 76 ]. The authors found that patients with low HALP scores had worse overall survival with mean OS of low HALP scores being 17.7 months compared to high HALP scores being 89.7 months ( p = 0.001), which was statistically significant in univariate and multivariate analysis as well.…”
Section: Introductionmentioning
confidence: 99%
“…Hemoglobin level and platelet count were factors that significantly affected this association. Ekinci et al performed a retrospective cohort study of 123 metastatic renal cell cancer patients and evinced that patients with high HALP scores had superior overall survival outcomes 14 . Albumin, which reflects the nutritional status, has been associated with the prognosis of renal cell carcinoma 15 .…”
Section: Discussionmentioning
confidence: 99%